Papel da pesquisa no desempenho recente da pecuária de corte no Brasil - Carlos Jose Zurita Cano (2008)
Recent development and tagging of productive variables in relation with beef cattle production were established. By using the Tornqvist index, contributions for the Brazilian beef cattle productivity were calculated. Some of these variables (Rations, mineral salt, medicines, fertilizers, defensive products and seeds) were used according to the Total factor productivity (TFP) principles and validated in a model considering the period of 1970 to 1996 (26 years). TPF was estimated in a level of 3% per year for beef cattle production. It was also concluded that changes in economic and technological levels of beef cattle in Brazil requires remodeling databases.